Penegakan Hukum Terhadap Pedagang Kaki Lima Di Kawasan Pantai Padang Berdasarkan Pasal 8 Peraturan Daerah No 11 Tahun 2005 Tentang Ketertiban Umum Dan Ketentraman Masyarakat - Meita Lefi Kunia; Boiziardi AS; Fitri Ardi (Fakultas Hukum Universitas Tamansiswa Padang, 2025)
Street vendors can be defined as traders who do not have a permanent or fixed business location. The existence of street vendors in the Padang coastal area, which is located in a densely urbanized area in the West Padang sub-district stretching from the Purus area to the Batang Arau estuary, West Sumatra. It is a serious problem for the Padang city government, this is because it can disrupt the order and comfort of road users and even cause congestion that affects the comfort of visitors and damages the beauty of the beach as one of the leading tourist attractions in Padang City. The problems discussed in this study are 1) How is the law enforcement against street vendors in the Padang coastal area who violate Regional Regulation No. 11 of 2005. The research method used is the Sociological research method, this type of research studies the law as an independent variable / cause that causes influence and consequences on various aspects of social life. This research is descriptive, namely, research that attempts to explain or describe a phenomenon. Data processing used is editing, coding and tabulating. The results of this study indicate that law enforcement carried out by the Public Order Agency (Satpol PP) involves confiscating carts, tables, and chairs from vendors who persist in operating in prohibited areas.